2006
DOI: 10.3354/dao069033
|View full text |Cite
|
Sign up to set email alerts
|

Coral diseases near Lee Stocking Island, Bahamas: patterns and potential drivers

Abstract: The number of coral diseases, coral species they infect, number of reported cases, and range over which these diseases are distributed have all increased dramatically in the past 3 decades, posing a serious threat to coral reef ecosystems worldwide. While some published studies provide data on the distribution of coral diseases at local and regional levels, few studies have addressed the factors that may drive these distributions. We recorded coral disease occurrence, prevalence, and severity along with temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 24 publications
5
69
1
Order By: Relevance
“…The second St. Croix site, Butler Bay, is nearby but up-current and not exposed to sewage (Kaczmarsky et al 2005). Field studies have shown that BBD disease prevalence was significantly higher (2.9%) in the reef site with direct sewage input as com- (Voss & Richardson 2006a). However, while the reefs of Lee Stocking Island are considered pristine, the environmental health of the Florida Keys reefs is a subject of much controversy.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…The second St. Croix site, Butler Bay, is nearby but up-current and not exposed to sewage (Kaczmarsky et al 2005). Field studies have shown that BBD disease prevalence was significantly higher (2.9%) in the reef site with direct sewage input as com- (Voss & Richardson 2006a). However, while the reefs of Lee Stocking Island are considered pristine, the environmental health of the Florida Keys reefs is a subject of much controversy.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…While it is possible that specific environmental factors are driving these differences, for example sewage input (Kaczmarsky et al 2005), higher water temperatures (Voss & Richardson 2006a), and elevated nutrients (Kuta & Richardson 2002, Voss & Richardson 2006b), these same drivers may be acting synergistically to promote the disease. In the long-term, an understanding of how individual pathogens and pathogenic communities interact with their hosts to cause disease will require physiological investigations of these pathogens in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence of BBD on previously infected colonies is common (Kuta & Richardson 1996;Voss & Richardson 2006;Rodriguez & Croquer 2008), suggesting that colonies which survive BBD may act as reservoirs for pathogens. While results suggest that 31 per cent of recurrent lesions in our study may have been caused by residual pathogens, we cannot distinguish whether recurrent BBD lesions observed at different sites than previous infections were caused by pathogens from the water column or by pathogens remaining on the colony that were motile and present at visually undetectable levels.…”
Section: (C) Data Analysesmentioning
confidence: 99%
“…Given potentially rapid rates of tissue loss caused by BBD, the disease is a potential threat to Indo-Pacific coral populations and warrants monitoring even in well-managed reef systems such as the GBR. Clumped BBD distribution patterns and apparent spread of disease to neighbouring colonies suggest that BBD is transmissible potentially through water movement and direct contact of colonies (Kuta & Richardson 1996;Voss & Richardson 2006), although specific transmission modes and mechanisms of band formation are still poorly understood. A range of micro-organisms have been identified from the characteristic disease band, including cyanobacteria, sulphate-reducing Desulfovibrio bacterial species, sulphide-oxidizing Beggiatoa bacterial species, a marine fungus and other heterotrophic microbes (reviewed in Richardson 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, however, little is known regarding how bacterial pathogens form the black band on host corals or how changes in microbial communities lead to onset of the disease. Given the potential for BBD to cause substantial tissue loss in coral populations (reviewed in Green and Bruckner, 2000;Sato et al, 2009) and the likelihood that effects of the disease will be exacerbated as seawater temperatures warm with predicted climate change Kuta and Richardson, 2002;Borger and Steiner, 2005;Voss and Richardson, 2006;Rodriguez and Croquer, 2008;Sato et al, 2009), there is need for greater understanding of early stages in the onset of the disease if BBD is to be managed effectively.…”
Section: Introductionmentioning
confidence: 99%